PENGARUH ETNOSENTRISME KONSUMEN TERHADAP PERSEPSI KUALITAS DAN NIAT BELI PRODUK AYAM TALIWANG (STUDI PADA RUMAH MAKAN TALIWANG I CAKRANEGARA) - Irpak Nasabi (Master of Management, Mataram University, 2017)
This research is aimed at analyzing the effect of consumers’ ethnocentrism on the perception of product quality and buying intention of ayam taliwang (a case study on Rumah Makan Taliwang I Cakranegara). This is quantitative study. The population are individual and community who already know the ayam taliwang product in Mataram. The sampel were 100 respondents selected through accidental sampling and analyzed using structural equation modeling (SEM). The research showed that cosumers’ etnosentrism had significant effect on the buying intention of ayam taliwang in Rumah Makan Taliwang I Cakranegara. The consumers’ etnosentrism had also effect on the perception of product quality which means that the more positive of consumers ethnocentrism the better the perception of product quality of ayam taliwang. Perception of product quality moderated the correlation between consumers’ ethnosentrism and buying intention, which means that the higher the perception of product quality, the stronger the correlation between consumers’ etnosentrism and buying intention. This research implied theoretically and managerially in the context of product of ayam taliwang in Rumah Makan Taliwang I Cakranegara. Keywords : consumers’ ethnosentrism, perception of product quality and buying intention.